Israel yearbook on human rights. Volume 48, 2018 - Dinstein, Yoram; Lahav, Jeff (Leiden ; Boston : Brill Nijhoff, 2018)
The Israel Yearbook on Human Rights- an annual published under the auspices of the Faculty of Law of Tel Aviv University since 1971- is devoted to publishing studies by distinguished scholars in Israel and other countries on human rights in peace and war, with particular emphasis on problems relevant to the State of Israel and the Jewish people.
From State Comptroller to National Human Rights Institution -- A Short but Necessary PathA Ray of Hope -- Woman's Education in the Arab World; III. ACADEMIC FREEDOM; Academic Ethics, State Regulation and Political Anarchism; IV. REFUGEES; Refugees and the State of Israel; V. SPECIAL ISSUES; UN Security Council Resolution 2334 (2016) -- An Analysis; JUDICIAL DECISIONS; Judgments of the Supreme Court of Israel Relating to Human Rights; LEGISLATION; The Counter-Terrorism Law, 5776-2016.
Online resource; title from PDF title page (EBSCO, viewed October 17, 2018).
Keywords: Human rights -- Periodicals; Civil rights -- Israel -- Periodicals; Civil rights -- Periodicals; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Civil rights; Human rights; Israel; Electronic books; Periodicals